2017
DOI: 10.1007/978-3-658-14785-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Mobility in the 20th Century

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…The former finding that a horizontal differentiation is already present at the lower layer of the social space is most likely due to educational expansion and the increased importance of cultural capital for lower social classes due to de-industrialization and new class divisions, e.g. between industrial and service occupations (Hertel 2017;Oesch 2006). The latter finding that the elite class is characterized by both the highest economic and cultural capital is more challenging to understand.…”
Section: Discussionmentioning
confidence: 99%
“…The former finding that a horizontal differentiation is already present at the lower layer of the social space is most likely due to educational expansion and the increased importance of cultural capital for lower social classes due to de-industrialization and new class divisions, e.g. between industrial and service occupations (Hertel 2017;Oesch 2006). The latter finding that the elite class is characterized by both the highest economic and cultural capital is more challenging to understand.…”
Section: Discussionmentioning
confidence: 99%
“…Weitere untersuchte Klassenschemen heben horizontale Unterschiede zwischen vertikal gegliederten Gruppen hervor. Die hier untersuchten Klassifizierungen von Oesch (2006Oesch ( , 2013 und Hertel (2017) beziehen sich unterschiedlich stark auf frühere, rein heuristische Unterscheidungen zwischen Mittelklassepositionen entweder entlang der Gegenüberstellung von fordistischen und postindustriellen…”
Section: Oesch Und Ipics: Berufsklassen Als Folgen Ausdifferenzierter Arbeitslogikenunclassified
“…Berufspositionen (Assimakopoulou, Esping-Andersen, & Van Kersbergen, 1992;Esping-Andersen, 1993) oder Ansätzen, die freie Berufe und Professionen mit Manager:innen und Administrator:innen kontrastieren (Gallie, White, Cheng, & Tomlinson, 1998;Kriesi, 1989;Müller, 1998 (Hertel, 2017;Oesch, 2013). Beschäftigten beeinflussen und innerhalb derselben Arbeitslogiken homogenisieren.…”
Section: Oesch Und Ipics: Berufsklassen Als Folgen Ausdifferenzierter Arbeitslogikenunclassified
See 1 more Smart Citation
“…Keeping these caveats in mind, it is important to note that we did not aim to provide a causal analysis of the relationship between inequality and mobility, but rather a conceptually innovative, descriptive account from a sociological perspective. Sociologists have only recently concluded that there has been a modest rise in social fluidity in most countries over the course of the prosperous decades following World War II (Breen 2004;Hertel 2017), but this subtle trend toward openness may mean little to individuals born in this era of increasing inequality. Although we cannot evaluate such a conjecture based on this analysis, we can state with certainty that current mobility chances are more unequally distributed in countries marked by larger between-class inequalities.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%